Structural changes in soybean seed coat due to harvest time and storage - Vieira, Bruno Guilherme Torres Licursi [UNESP]; Barbosa, Giselle Feliciani [UNESP]; Barbosa, Rafael Marani [UNESP]; Vieira, Roberval Daiton [UNESP] (My University, 2013)
In the field, seeds are subject to various factors that can compromise their physiological potential before and during harvesting, drying, processing, storage and sowing. The present study was conducted in order to monitor deterioration and to analyze soybean seed coat morphology during storage. Soybean [Glycine max (L.) Merrill] seeds of cultivar MG/BR-46 Conquista were harvested at three different times (physiological maturity development stage R7, R7 + 7 days and R7 + 15 days) and stored in either cold room at 10°C, 45-50% air relative humidity (RH) or climatic chamber at 25°C, 60- 75% RH. After the storage period, seeds were electromicrographed using Scanning Electron Microscopy (SEM), and the seed physiological potential was evaluated using germination (rolled paper and sand) and vigor (electrical conductivity, tetrazolium, accelerated aging and seedling field emergency) tests. Seed moisture content was also determined. To perform the electron micrographs, transversal cuts were made in seeds coated with gold. Cuts in the seed coat showed highly organized structures, with cuticle, epidermis (palisade or macrosclereid cells), hypodermis (hourglass, pillar or osteosclereid cells) and parenchymal cells. Storage under adverse conditions in the field for periods greater than the R7 developmental stage and in the climatic chamber at 25oC for 12 months reduced physiological potential by damaging the seed coat structure; however, physiological potential was maintained at 10oC (45-50% RH) for 12 months in a cold room.
Keywords: Coat; Glycine max (L.) Merrill; Physiological potential; Seeds; Storage; Vigor test; tetrazolium; cuticle; electric conductivity; germination; harvest period; humidity; moisture; nonhuman; plant epidermis; plant parenchyma cell; scanning electron microscopy; seed husk; seed storage; seedling emergence; soybean; subcutaneous tissue; water content